Safeguarding of Fetal Growth by Mast Cells and Natural Killer Cells: Deficiency of One Is Counterbalanced by the Other - Meyer, Nicole; Woidacki, Katja; Maurer, Marcus; Zenclussen, Ana Claudia (Frontiers in Immunology, 2017)
Uterine natural killer cells (uNKs) and mast cells (uMCs) are of crucial importance for spiral artery (SA) remodelling and placentation. Mice deficient for both NKs and MCs including uNKs and uMCs show markedly impaired SA remodeling and their fetuses are growth-retarded. In contrast, the absence of either NKs or MCs results in only minor impairment. This suggests that uNKs can compensate for the effects of uMCs on SA remodeling and vice versa. To test this hypothesis, we assessed uNK numbers in uMC-deficient mice as well as uMC numbers in uNK-depleted mice. Notably, uMC-deficient C57BL/6J-KitW-sh/W-sh (W-sh) mice showed markedly increased numbers of uNKs in contrast to wild type (WT), and the transfer of bone marrow-derived MCs (BMMCs) reverted this phenotype. Vice versa, uNK-deficient C57BL/6NTac-IL15tm1ImxN5 (IL-15-/-) mice had significantly increased numbers of uMCs and MC-specific proteases. Our results suggest that uNKs and uMCs can counterbalance their effects at the feto-maternal interface and jointly promote SA remodelling and placentation.